2018
DOI: 10.1016/j.cub.2018.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory Control of Orientation in Tethered Flying Drosophila

Abstract: Summary A longstanding goal of systems neuroscience is to quantitatively describe how the brain integrates sensory cues over time. Here we develop a closed-loop orienting paradigm in Drosophila to study the algorithms by which cues from two modalities are integrated during ongoing behavior. We find that flies exhibit two behaviors when presented simultaneously with an attractive visual stripe and aversive wind cue. First, flies perform a turn sequence where they initially turn away from the wind and but later … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 56 publications
(84 reference statements)
1
28
1
Order By: Relevance
“…1F). While response magnitudes no doubt depend on stimulus intensity (airflow velocity, stripe contrast, and odor concentration), we know that our visual and airflow cues elicit orienting responses of approximately equal magnitude in a flight simulator (Currier and Nagel, 2018).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…1F). While response magnitudes no doubt depend on stimulus intensity (airflow velocity, stripe contrast, and odor concentration), we know that our visual and airflow cues elicit orienting responses of approximately equal magnitude in a flight simulator (Currier and Nagel, 2018).…”
Section: Resultsmentioning
confidence: 90%
“…This turn signal drives rotations of an airflow tube, allowing flies to control their orientation with respect to that flow. In previous experiments, we observed that flies prefer to orient away from the source of flow (Currier and Nagel, 2018). are relative to the hemisphere of connected ventral P-FN cell bodies.…”
Section: Ventral P-fns Are Required To Orient To Airflow In Tetheredmentioning
confidence: 80%
“…1A & 1B,right). Flies fixate vertical stripes while walking and in flight (Reichardt and Poggio, 1976;Heisenberg and Wolf, 1979;Maimon et al 2008) and tend to orient away from an airflow source (Currier andNagel 2018, Kaushik et al, 2020). The addition of an attractive odorant to airflow switches orientation from downwind to upwind (van Bruegel et al 2014, Alvarez-Salvado 2018.…”
Section: Resultsmentioning
confidence: 99%
“…Stimulus delivery was achieved by a modified version of a perviously used system (Currier and Nagel, 2018).…”
Section: Stimulus Deliverymentioning
confidence: 99%
“…In contrast to beetles, which orient in any direction relative to the wind ( Fig. 2E), tethered flying fruit flies rather exhibit an anemotactic behavior when tested in the presence of an apparent wind stimulus (35,36). A strong deflection of the antennae, generated by fast self-motion, most likely prevents dung beetles from using their wind compass when moving through the air.…”
Section: Dung Beetles Use a Dynamic Multimodal Compass System For Strmentioning
confidence: 94%